CEBPA mutants down-regulate AML cell susceptibility to NK-mediated lysis by disruption of the expression of NKG2D ligands, which can be restored by LSD1 inhibition. (31st December 2022) - Liu, Meng; Du, Mengbao; Yu, Jian; Qian, Zijun; Gao, Yang; Pan, Wenjue; Zhao, Xiujie; Wang, Mowang; Li, Huimin; Zheng, Jiaqi; Huang, Qianshuo; Wang, Li-Mengmeng; et al.
ABSTRACT: NK group 2, member D (NKG2D) is one of the most critical activating receptors expressed by natural killer (NK) cells. There is growing evidence that acute myeloid leukemia (AML) cells may evade NK cell-mediated cell lysis by expressing low or no ligands for NKG2D (NKG2D-Ls). We hypothesized that CCAAT/enhancer-binding protein α (C/EBPα), one of the most studied lineage-specific transcription factors in hematopoiesis, might influence the expression of NKG2D-Ls. To test this hypothesis, we first examined the endogenous expression of wild-type C/EBPα (C/EBPα-p42) in human AML cell lines and demonstrated that its expression level was highly relevant to the sensitivity of AML cells to NK cell cytotoxicity. Induction of C/EBPα-p42 in the low endogenous CEBPA- expressing AML cell line increased the sensitivity to NK-induced lysis. Moreover, decreased expression of C/EBPα-p42 by RNA interference in AML cells abrogated NK-mediated cytotoxicity. We further showed that the increase in NK susceptibility caused by C/EBPα-p42 occurred through up-regulation of the NKG2D-Ls ULBP2/5/6 in AML cells. More importantly, chromatin immunoprecipitation (ChIP) coupled with high-throughput sequencing captured C/EBPα motif signatures at the enhancer regions of the ULBP 2/5/6 genes. Whilst, the AML-associated C/EBPα C-terminal mutant and N-terminal truncated mutant (C/EBPα-p30) diminished ULBP2/5/6 transcription. Finally, we identified that histone demethylase lysine-specific demethylase 1 (LSD1) inhibition can restore the expression of ULBPs via induction of CEBPA expression in AML cells, which may represent a novel therapeutic strategy for CEBPA -mutated AML. Abbreviations: C/EBPα: CCAAT/enhancer-binding protein α; TF: Transcription factor; AML: Acute myeloid leukemia; TAD: Transactivation domain; FS: Frameshift; NK: Natural killer; NKG2D: NK group 2, member D; NKG2D-Ls: Ligands for NKG2D; MHC: Major histocompatibility complex; MICA: MHC class I-related chain A; ULBP: UL16-binding protein; STAT3: Signal transducer and activator of transcription 3; LSD1: Lysine-specific demethylase 1; Ab: Antibody; PBMC: Peripheral blood mononuclear cell; PBS: Phosphate-buffered saline; CFSE: Carboxyfluorescein diacetate succinimidyl ester; PI: Propidium iodide; shRNA: Short hairpin RNA; ChIP: Chromatin immunoprecipitation; BM: Binding motif; HCNE: Highly conserved noncoding element; TSS: Transcription start site; HMA: Hypomethylating agent; AZA: Azacitidine/5-azacytidine; DAC: Decitabine/5-aza-29-deoxycytidine; 2-PCPA: Tranylcypromine; RBP: RNA-binding protein; MSI2: MUSASHI-2; HDACi: Inhibitor of histone deacetylases; VPA: Valproate; DNMTi: DNA methyl transferase inhibitor; SCLC: Small cell lung cancer